Handover Rate Analysis for K-Tier Heterogeneous Cellular Networks With General Path-Loss Exponents - Ren, Yuwei; Li, Yingzhe; Qi, Can (IEEE communications letters, 2017)
Network densification will produce frequent handover for mobile users, which could largely diminish the densification gain. We develop a comprehensive analytical model for the handover rate in K-tier heterogeneous cellular networks, where each tier is modeled as an independent Poisson point process with unique transmit power, path-loss exponent, spatial density, and association bias. The spatial randomness of users' mobility is captured and analyzed by stochastic geometric theory, and we derive closed-form expressions for handover rate with arbitrary mobile trajectories. The relationship between total handover rate and horizontal/vertical handover rate is analyzed, and the effect of the user's velocity, BS densities, path-loss exponents, and association bias are found. There is an optimum value of BS densities to keep a good tradeoff between handover rate and user's throughput. Finally, simulation results verify the accuracy of the derivation.